Customer Requirements on Digital Application in Energy Sectors for B2B Customers (a Part of Quality Function Deployment Analysis on My Pertamina for Business) - Rama Hendi Prastiyo; Laura Lahindah (Pusat Publikasi Nusantara, 2024)
This study is willing to reveal what are the B2B customers requirement for My Pertamina for Business digital application that they have been using. They are also leaded to evaluate the application performance and reveal what are the resistances in using the application. Literature review and interview are conducted. Seven respondents are involved in the study. They come from three different customer clusters, that are aviation, retail and industrial and marine. The results reveal that customer requirements of B2B customer from digital application in energy sectors are 1) price Simulation, 2) ordering product to create sales order, 3) monitoring tax invoice, 4) monitoring withholding tax slip, 5) the relevance of the displayed energy product to the customer needs, 6) providing many function in one application, 7) connected to direct debit of bank system, 8) connected to other digital platform, 9) forecasting the fuel price, 10) monitoring invoices, 11) energy related news portal and 12) contact center to buy other energy products; 13) reward and discount; and 14) playing entertainment platform such as online game and podcast. Overall performance of the application satisfy the customers but point 7,8,9,10,11,12 and 14 of customer requirements are not fulfilled yet. Dealing with the customer resistance in using the application are slow response of customer complain handling, inaccurate information related to drum stock in the application and in the aviation fuel terminal, and less updated of monitoring Credit/Debit Reversal notes